Sustainability analysis of a transport system: the UK car fleet, 1995-2005 - Smith, T (2012)
A sustainability analysis was performed on the UK car fleet in 1995 and 2005, which showed that the sustainability of the car fleet improved by 13% over the time period. The Process Analysis Method was applied to generate a reliable, consistent, and sufficient indicator set describing the sustainability impact of a transport system. As well as identifying conventional impacts, this analysis identified that the quality of the mobility produced has an important impact on sustainability. Quality affects how well mobility meets human needs, but also influences user choices, which drive system change. It is suggested that the indicator set that was produced should form the basis for future sustainability assessments. A study was carried out on the UK car fleet in 1995 and 2005 to test the indicator set and to investigate changes in environmental, human/social and economic sustainability over the period. Distance travelled increased, driven by a 28% increase in fleet size, which counteracted increases in fuel efficiency. Weight also increased, driven by increasing vehicle size, and additional safety and comfort-related features, increasing embodied energy and emissions. However, direct emissions of non- CO2 pollutants reduced due to increasingly stringent regulation, as did waste to landfill. CO2 emissions increased by 11% overall. The reduction in emissions had a positive impact on health, with emission related mortality reducing by 27%. Casualties from collisions involving cars reduced by 13%. Road accidents were found to represent an impact on mortality three times greater than emissions. The indicators of service quality showed a drop in average speed and reliability (from both the network and vehicle perspectives) but an increase in comfort and vehicle safety. The increase in fleet size and new registrations drove growth in the retail and maintenance sector, which saw growth of 25% in gross value added. The opposite happened to the manufacturing sector, which shrank by 26%, due to stagnant domestic production and an increasingly competitive market affecting profit margins. An indicator aggregation was performed to summarise changes in the sustainability of car-based mobility. The indicators were normalised to a percentage change, and weighted according to their monetary value.